Cover Feature: Fast and Efficient Postsynthetic DNA Labeling in Cells by Means of Strain‐Promoted Sydnone‐Alkyne Cycloadditions (Chem. Eur. J. 65/2021). Issue 65 (10th November 2021) - Krell, Katja; Pfeuffer, Bastian; Rönicke, Franziska; Chinoy, Zoeisha S.; Favre, Camille; Friscourt, Frédéric; Wagenknecht, Hans‐Achim
Abstract : DNA strands, modified with the novel bioorthogonal reporter sydnone, undergo fast and efficient labeling with cyclooctyne–dye conjugates, both in vitro and in HeLa cells. These results show that sydnones are versatile bioorthogonal tags and have the premise to become essential tools for tracking DNA and potentially RNA in living cells. More information can be found in the Communication by F. Friscourt, H.‐A. Wagenknecht et al. (DOI: 10.1002/chem.202103026 ).